2017
DOI: 10.1017/s1041610217001090
|View full text |Cite
|
Sign up to set email alerts
|

Use of psychotropic medications in relation to neuropsychiatric symptoms, cognition and functional performance in Alzheimer's disease over a three-year period: Kuopio ALSOVA study

Abstract: Psychotropic medication use increased significantly in relation to increasing dependency in AD, especially with NPS. Furthermore, the use of antipsychotics increased with disease severity, and with decline in daily functioning. Cognitive performance was not associated with psychotropic medication use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…Furthermore, another team examined patients with recently diagnosed mild AD which were treated with antidementia medications such as acetylcholinesterase inhibitors (donepezil, galantamine, rivastigmine) and memantine. The authors reported an association between AD and an increased use of psychotropic drugs (Törmälehto et al, 2017). However, the administration of psychotropic medications was not related to alterations in cognitive performance (Törmälehto et al, 2017).…”
Section: Cohort Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, another team examined patients with recently diagnosed mild AD which were treated with antidementia medications such as acetylcholinesterase inhibitors (donepezil, galantamine, rivastigmine) and memantine. The authors reported an association between AD and an increased use of psychotropic drugs (Törmälehto et al, 2017). However, the administration of psychotropic medications was not related to alterations in cognitive performance (Törmälehto et al, 2017).…”
Section: Cohort Studiesmentioning
confidence: 99%
“…The authors reported an association between AD and an increased use of psychotropic drugs (Törmälehto et al, 2017). However, the administration of psychotropic medications was not related to alterations in cognitive performance (Törmälehto et al, 2017). Finally, Grande and collaborators showed that patients treated with short-and long-acting BZDs presented adjusted MMSE mean scores of 25.4; 95% CI 25.1-25.7, while non-treated patients had 25.9; 95% CI 25.3-26.4 (short acting BZDs); 25.3; 95% CI 25.2-25.5 (long-acting BZDs); (p = 0.156) (Grande et al, 2019).…”
Section: Cohort Studiesmentioning
confidence: 99%
“…[42] A one-point NPI increase was associated with an increase of the odds of using any psychotropic medication class by 4% (OR=1.04, 95% CI=1.01-1.07) in a 3-year prospective trial of home-dwelling persons with AD and their caregivers (N=236 dyads). [43] High NPI scores predicted subsequent hypo-metabolism in the posterior cingulate cortex over 2 years in individuals with preclinical AD (both amyloid and tau pathologies present), but not in asymptomatic at risk for AD. [44] Sleep/nighttime behavior disorders and irritability-lability were the domains of the NPI that correlated most with the metabolic dysfunction in preclinical AD.…”
Section: Results Of the Reviewmentioning
confidence: 93%
“…Indirect costs of AD are derived from decreasing professional performances and absenteeism in family members, discomfort in carers relationship, and even onset of psychiatric or psychosomatic disorders in caregivers. According to a meta-analysis that included 17 trials, the aggregate prevalence of depression among caregivers was 34% (odds of having depression is 1.53 times higher in female caregivers, 1.86 times higher in caregivers to male care-recipients, and 2.51 times higher in spousal caregivers), anxiety 43.6%, and the use of psychotropic drugs 27.2%. [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, we found no association between the Neuropsychiatric Inventory sub-syndrome affective symptoms score and psychotropic drug use, suggesting that antidepressants were not prescribed for persons with only depressive symptoms. T€ orm€ alehto et al found that the use of antidepressants in home-dwelling people with late-onset Alzheimer's dementia was weakly correlated with the score on the Neuropsychiatric Inventory or the score on the depression scale that was used (Tormalehto, Martikainen, Bell, Hallikainen, & Koivisto, 2017). Research shows that antidepressants should have no place in people with dementia and mild or moderate depressive symptoms because this treatment shows little or no reduction in depressive symptoms and has little impact on activities in daily life (Banerjee et al, 2011;Dudas et al, 2018;Zuidema et al, 2018).…”
Section: Discussionmentioning
confidence: 99%